Enlaces - Becker Ravest, Alex (AUS - Arquitectura / Urbanismo / Sustentabilidad, 2017)
http://www.sistematoha.cl/aplicacionesycostos.htm http://ecoportal.net/nosotros http://www2.csostenible.net/es_es/inicio/pages/index.aspx http://habitat.aq.upm.es/ http://www.passivehouse.com/